Teknik Aplikasi Pupuk Hayati (Been Sae) Pada Tanaman Padi di BPP Meureubo - Jasmi, Jasmi; Dewi, Huri Afrina; Gunawan, Aristotel; Rosmeri, Rosmeri (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
This community service activity was carried out with the aim of providing information to farmer groups regarding the benefits and uses as well as the application of Been Sae biofertilizer. In addition, other objectives are also one of the Tridharma activities for the writer. The stages of implementing this community service activity are a form of counseling about the technical application of Been Sae's biological fertilizer to rice plants (Oriza Sateva, L). to improve the physical, chemical and biological properties of the soil in order to increase crop production and maintain the binding capacity of groundwater to nutrients while at the same time suppressing disturbing elements. This community service activity was carried out at the Farmer Group in the village of Mesjid Tuha Meurebo District. The exact time and method of fertilization must be known, including: The rules for using Been Sae fertilizer are by dissolving 10 ml of Been sae in 1 liter of water, stirring thoroughly, then placing it in a tube (spray tank/sprayer), spraying it on the soil or roots. For Hatchery; the seeds are soaked with Been sae solution as much as 3 ml/liter of water for 30 minutes, then aired to dry, after drying the seeds can be planted. Maintenance is carried out by spraying Been sae a week after planting with a dose of 2 liters/200 liters of water/Ha of soil, then spraying the plants and soil every 2/week, Beensae can be used as a decomposer mixture in making compost. The conclusion from this activity is that farmers know more about the benefits and uses of Been Sae biofertilizer.